Are bony pelvis dimensions associated with levator ani defects? A case–control study - Berger, Mitchell B. (2013)
INTRODUCTION AND HYPOTHESIS: Bony pelvis dimensions have been shown to differ in women with and without pelvic floor dysfunction. The goal of this study was to determine whether bony pelvis dimensions are different when comparing women with severe bilateral levator ani defects (LAD) with those with normal muscles. METHODS: This is a secondary analysis of a case–control study comparing women with and those without pelvic organ prolapse. Subjects underwent pelvic organ prolapse quantification (POP-Q) examination and were classified as either having prolapse or being normal. All underwent pelvic magnetic resonance imaging (MRI). Levator defects were assessed based on the muscles’ appearance on imaging and subjects were stratified into two groups—women with normal muscles (n=99) and women with severe bilateral LAD (n=50). Bony pelvis dimensions were measured via MRI pelvimetry. The subpubic angle, interspinous and intertuberous diameters, and the sacrococcygeal joint-to-infrapubic point (SCIPP) lengths were compared. RESULTS: Both groups had similar demographics. The SCIPP length was 2.5 % (3 mm) shorter in women with severe LAD than in those without defects (P=0.02). The SCIPP measured 4 % (5 mm) less in women with prolapse and severe LAD than in subjects with prolapse but normal muscles (P=0.01). Logistic regression identified SCIPP length and history of forceps delivery as being independent predictors of severe bilateral LAD. CONCLUSIONS: Severe bilateral LAD are associated with shorter SCIPP length and forceps-assisted vaginal delivery.